The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.smr.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Doping in sport: Whose problem is it?

Abstract: In the last few years there has been a significant increase in the number and scope of social science research into doping in sport. However, despite this apparent progress, the field remains a disparate body of work and lacks both direction and leadership. Whilst sport management is a discipline that is well suited to provide such leadership, scholarly research into this controversial topic has not been published widely in sport management journals.This special issue aims to redress this gap by bringing toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
(35 reference statements)
2
4
0
2
Order By: Relevance
“…Within these attitudes there is a relationship between the level of permissiveness towards doping and whether the participants had been urged to take these substances, and we found that the individuals who had been so urged at some point show higher acceptance of the use or consumption of these substances. These results match those of similar studies performed previously (Engelberg & Skinner, 2016;Copeland & Potwarka, 2016;Barkoukis, Tsorbarzoudis & Rodafinos, 2013), which revealed the importance of individuals' milieu or social relations and their attitudes towards doping. A study with similar features performed by Woolf, Rimal and Sripad (2013) inquired into the possible causes of the use of anabolic steroids or other steroids in young people; 404 adolescent athletes participated in this study, which found that the norms and judgements of their friends or teammates are one of the factors that has most influence on the decision to use performance-enhancing drugs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Within these attitudes there is a relationship between the level of permissiveness towards doping and whether the participants had been urged to take these substances, and we found that the individuals who had been so urged at some point show higher acceptance of the use or consumption of these substances. These results match those of similar studies performed previously (Engelberg & Skinner, 2016;Copeland & Potwarka, 2016;Barkoukis, Tsorbarzoudis & Rodafinos, 2013), which revealed the importance of individuals' milieu or social relations and their attitudes towards doping. A study with similar features performed by Woolf, Rimal and Sripad (2013) inquired into the possible causes of the use of anabolic steroids or other steroids in young people; 404 adolescent athletes participated in this study, which found that the norms and judgements of their friends or teammates are one of the factors that has most influence on the decision to use performance-enhancing drugs.…”
Section: Discussionsupporting
confidence: 92%
“…Dentro de estas actitudes se aprecia la relación existente entre el nivel de permisividad hacia el dopaje con si se les ha instado alguna vez al consumo de dichas sustancias, encontrando que los individuos a los que se les había sugerido el dopaje alguna vez tienen una mayor aceptación del uso o consumo de dichas sustancias; estos resultados coinciden con los de estudios similares realizados con anterioridad (Engelberg & Skinner, 2016;Copeland & Potwarka, 2016;Barkoukis, Tsorbarzoudis & Rodafinos, 2013), en los que se puede apreciar la importancia que representan el entorno o las relaciones sociales de los individuos en relación con las actitudes hacia el dopaje que estos tienen. En una investigación de similares características realizada por Woolf, Rimal y Sripad (2013), se indagó sobre las posibles causas del uso de anabolizantes o esteroides en jóvenes, y en la que participaron 404 atletas adolescentes, llegando a la conclusión de que las normas y juicios que siguen los amigos o compañeros de equipo de los jóvenes son uno de los aspectos que influyen en gran medida a la hora de tomar la decisión de usar sustancias dopantes.…”
Section: Discussionunclassified
“…Consequently, the need to understand the effectiveness of current anti-doping policy has become a central concern in sport policy and management research (Engelberg and Skinner 2016). There is growing interest in the historical development of anti-doping policy to understand contemporary anti-doping policy effectiveness (e.g., Hunt et al 2012, Gleaves and Llewellyn 2014, Ritchie 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios de caso con base en los más sonados escándalos del dopaje en el deporte, ofrecen una posibilidad de aprendizaje, 83 al igual que los enfoques interdisciplinarios que brindan explicaciones sobre la legitimidad de las instituciones que hacen parte del campo deportivo. 84 Todos estos esfuerzos pretenden posicionar la educación antidopaje como una prioridad para los responsables de la toma de decisiones dentro de las organizaciones deportivas [85][86][87] y un eje central en la formación de profesores. 88 • En la categoría 3.…”
Section: Resultados Y Análisisunclassified